PhD studies in transition conditions – the basis for the educational system and economic development: a case study Serbia - Živković, Živan; Panić, Marija (Serbian Journal of Management, 2024)
The quality of PhD studies is a key factor in an educational system that depends on human resources development as the basis for society's development in the 21st century. This paper used the Multiple Criteria Decision Support (MCDS) and voting methods in the SWOT environment, along with the hybrid SWOT-AHP method, to assess the quality of PhD studies in Serbia. Through expert analysis within the SWOT-AHP hybrid model, the determinants of SWOT subfactors and possible strategic options were defined, and the prioritization of defined strategies was determined, with the application of which all the current weaknesses of PhD studies in Serbia can be eliminated, and the path to reaching the level of quality defined by EU standards can be defined. This study aims to direct the scientific public's attention to the declining trend in the quality of PhD studies in Serbia and its consequences.
Keywords: PhD studies; quality; outcomes; AHP; SWOT